1999
DOI: 10.1099/13500872-145-8-1967
|View full text |Cite
|
Sign up to set email alerts
|

A simplified subtractive hybridization protocol used to isolate DNA sequences specific to Xylella fastidiosa

Abstract: showing no hybridization to the driver DNA, was used as a probe specific to Xy. fastidiosa from citrus and oleander. This fragment was sequenced and the predicted protein showed 40% similarity to the central region of flagellin of Escherichia co/i serotypes H1 and H12. A pair of internal primers (f14-1 and f14-2) was designed for amplification of Xy. fastidiosa DNA. These primers detected Xy. fastidiosa strains isolated from citrus and oleander and yielded an amplification product of about 600 bp. They were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Improving detection of the pathogen will enhance the study of the interaction between host plants and the pathogen. A better sample-collection technique could improve the sensitivity of current detection techniques (2,13,14,16,21,35). Vacuum extraction of xylem sap has been used to identify bacteria in grapevine (4).…”
Section: Comparison Of Whole-tissue and Xylem Fluid Collection Technimentioning
confidence: 99%
See 1 more Smart Citation
“…Improving detection of the pathogen will enhance the study of the interaction between host plants and the pathogen. A better sample-collection technique could improve the sensitivity of current detection techniques (2,13,14,16,21,35). Vacuum extraction of xylem sap has been used to identify bacteria in grapevine (4).…”
Section: Comparison Of Whole-tissue and Xylem Fluid Collection Technimentioning
confidence: 99%
“…Detection methods currently used include enzyme-linked immunosorbent assay (ELISA; 3,6,23,33,34), polymerase chain reaction (PCR; 2,7,8,14,[23][24][25]34), and culturing from infected tissue (10)(11)(12)29). Several problems still exist with these methods, mainly stemming from low titer of bacteria in samples, resulting in inconsistent detection (7,8,23,25,33,34).…”
Section: Comparison Of Whole-tissue and Xylem Fluid Collection Technimentioning
confidence: 99%
“…O uso de métodos de diagnósticos para identificar a presença de X fastidiosa em plantas é um passo importante na implementação de medidas de restrição da disseminação da doença no campo e em áreas não infectadas (Ferreira et al, 1999).…”
Section: Diagnóstico De X Fastidiosaunclassified
“…Acidovorax, Burkholderia, Erwinia, Herbaspirillum, Liberbactor, Pseudomonas, Ralstonia, Xanthomonas, and Xylella have been shown to be plant pathogens (Ferreira et al, 1999;). Some recent studies have shown that there are other prokaryotic pathogens found in the sieve tubes of plants (Ali et al, 1991;.…”
Section: Other Pathogenic Prokaryotesmentioning
confidence: 99%
“…There are numerous other plant diseases that are caused by bacteria (Ferreira et al, 1999;Hocquellet et al, 1999, Hu and.…”
Section: Chapter6 Conclusionmentioning
confidence: 99%